CRYOVOLCANISM AND THE MYSTERY OF THE PATOM CONE - Vladimir R. Alekseyev (Геодинамика и тектонофизика, 2015)
In the Earth’s regions with cold climate, cryovolcanism is widespread. This phenomena is manifested as eruptions of material due to freezing of closed-type or open-type water-bearing systems which is accompanied by generation of effusive topographic forms, such as «pingo». The Patom cone is a typical structure created by cryovolcanism in fractured bedrocksof the Proterozoic age. The cone was shaped a result of the long-term, possibly multistage freezing of the hydrogeological structure during continuous and complicated phase of cryo- and speleo-genesis. The ice-saturated breccia containing limestone, sandstone and shale, which composed the cone, was subject to slow spreading due to its plastic properties; the top of the mound developed into a subsidence cone bordered by ring-shaped ramparts and a knoll in the middle, while thelongitudinal profile took on an asymmetric form. The absence of soil and vegetation cover on the surface of the cone, and a relatively weak degree of weathering of the rudaceous deposits bear no evidence that the geological object is young. The question as to the age of the cone is still open.